Persistence of Organo-Chlorine Pesticides in Groundwater of Jhansi City, India. - MARIAM, LUBNA; SINGH, ANJU; GUPTA, CHITRA (Asian Journal of Chemistry, 2010)
Organochloro pesticides have been analyzed in the groundwater samples collected from different sites. The most commonly used organochloro pesticides of the region were identified and analyzed in the groundwater samples at various site. The estimation of organochloro pesticides was done by gas chromatographic analysis. Among organochloro pesticides analyzed, the sorption decreased in the order of endosulfan > BHC > DDT; however, the leaching order is reverse.